2021
DOI: 10.3389/fendo.2021.716431
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids Produced by White Adipose Tissue Modulate Lipolysis in Lean but Not in Obese Rodent and Human

Abstract: White adipose tissue (WAT) possesses the endocannabinoid system (ECS) machinery and produces the two major endocannabinoids (ECs), arachidonoylethanolamide (AEA) and 2-arachidonoylglycerol (2-AG). Accumulating evidence indicates that WAT cannabinoid 1 receptors (CB1R) are involved in the regulation of fat storage, tissue remodeling and secretory functions but their role in controlling lipid mobilization is unclear. In the present study, we used different strategies to acutely increase ECS activity in WAT and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Further, an increase in the endocannabinoid tone in adipose tissue is associated with a dysregulation of adipocyte metabolism, thus, promoting fat mass expansion and related disorders [52][53][54][55][56]. In line with this, we recently indicated that activation of ECS in adipose tissue decreased lipolysis [57,58]. Here, we interestingly observed that JM-00266 treatment potentiates ß3 adrenergic receptor-stimulated lipolysis in vivo suggesting this compound might improve fat mobilization targeting adipose tissue CB1R.…”
Section: Discussionsupporting
confidence: 69%
“…Further, an increase in the endocannabinoid tone in adipose tissue is associated with a dysregulation of adipocyte metabolism, thus, promoting fat mass expansion and related disorders [52][53][54][55][56]. In line with this, we recently indicated that activation of ECS in adipose tissue decreased lipolysis [57,58]. Here, we interestingly observed that JM-00266 treatment potentiates ß3 adrenergic receptor-stimulated lipolysis in vivo suggesting this compound might improve fat mobilization targeting adipose tissue CB1R.…”
Section: Discussionsupporting
confidence: 69%
“…The endocannabinoid system (ECS) is a complex network ubiquitously expressed throughout the body. The best studied endocannabinoids (EC) N-arachidonylethanolamide (anandamide; AEA) and 2-arachidonoylglyerol (2-AG) are synthesized from membrane phospholipids, with fat depots providing an important source for plasma EC 1 . Due to their amphiphilic character, EC can modulate the activity of many membrane proteins and activate the G protein-coupled cannabinoid receptors 1 and 2 (CB 1 and CB 2 ) or the G protein-coupled receptor 55 (GPR55), all of them expressed at the cell surface 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…CB 1 activation was found to stimulate lipogenesis (Matias et al, 2006; Osei‐Hyiaman et al, 2005). Accordingly, increased cannabinoid tone (induced by treatment with the dual inhibitor of the endocannabinoids degrading enzymes) decreased the fat mobilization and lipolysis via a CB 1 ‐ and Akt‐dependent mechanism in vitro (rat and lean human) and in vivo (lean mice) (Buch et al, 2021). CB 1 antagonism increased adipocyte lipolysis, adiponectin expression, and oxygen consumption, together with improved glucose handling (Dong et al, 2018; Gary‐bobo et al, 2006; Han et al, 2019; Hildebrandt et al, 2003; Irwin et al, 2008; Jorgačević et al, 2019; Lipina et al, 2016; Mehrpouya‐bahrami et al, 2019; Murumalla et al, 2011; Nam et al, 2012; Paszkiewicz et al, 2020).…”
Section: Cannabinoid System and Muscle Homeostasis: Paths And Challengesmentioning
confidence: 99%
“…This latter is a mitochondrial protein found in brown adipose tissue and is responsible for nonshivering thermogenesis. It should be noted that cannabinoid signaling might be differentially regulated in lean and obese adipose tissue, as it was shown that CB 1 antagonism decreased lipolysis in “lean” adipose tissue but not in “obese” adipose tissue, for example, due to CB 1 desensitization (Buch et al, 2021; Mølhøj et al, 2010).…”
Section: Cannabinoid System and Muscle Homeostasis: Paths And Challengesmentioning
confidence: 99%